Appropriating Video Surveillance for Art and Environmental Awareness: Experiences from ARTiVIS. - Mendes, Mónica; Ângelo, Pedro; Correia, Nuno; Nisi, Valentina (Science & Engineering Ethics, 2018)
Arts, Real-Time Video and Interactivity for Sustainability (ARTiVIS) is an ongoing collaborative research project investigating how real-time video, DIY surveillance technologies and sensor data can be used as a tool for environmental awareness, activism and artistic explorations. The project consists of a series of digital contexts for aesthetic contemplation of nature and civic engagement, aiming to foster awareness and empowerment of local populations through DIY surveillance. At the core of the ARTIVIS efforts are a series of interactive installations (namely B-Wind!, Hug@tree and Play with Fire), that make use of surveillance technologies and real-time video as raw material to promote environmental awareness through the emotion generated by real-time connections with nature. Throughout the project development, the surveillance concept has been shifting from the use of surveillance technology in a centralized platform, to the idea of veillance with distributed peer-to-peer networks that can be used for science and environmental monitoring. In this paper we present the history of the ARTiVIS project, related and inspiring work, describe ongoing research work and explore the present and future challenges of appropriating surveillance technology for artistic, educational and civic engagement purposes.